Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1021/acsaem.8b00315
|View full text |Cite
|
Sign up to set email alerts
|

Simple Layer-by-Layer Assembly Method for Simultaneously Enhanced Electrical Conductivity and Thermopower of PEDOT:PSS/ce-MoS2 Heterostructure Films

Abstract: The organic/inorganic composites are considered as a promising strategy to gain high thermoelectric (TE) performance. Although many efforts have been focused on composites, complicated methods are real hindrance to the development of TE materials. Here, we demonstrate a potential TE thin film comprising highly conductive poly­(3,4-ethylenedioxythiophene):poly­(styrenesulfonate) (PEDOT:PSS) and chemically exfoliated MoS2 (ce-MoS2) nanosheets by layer-by-layer (LbL) assembly method. This work achieves the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 70 publications
2
29
0
Order By: Relevance
“…As a potential high-performance thermoelectric material, conductive polymers exhibit unique advantages such as a low thermal conductivity, flexibility, lightweight, and efficient solution processability [9,[198][199][200][201][202]. However, more work needs to be done to further improve their thermoelectric performance to use them in flexible and wearable thermoelectric devices.…”
Section: D Materials In Polymer Thermoelectric Materialsmentioning
confidence: 99%
“…As a potential high-performance thermoelectric material, conductive polymers exhibit unique advantages such as a low thermal conductivity, flexibility, lightweight, and efficient solution processability [9,[198][199][200][201][202]. However, more work needs to be done to further improve their thermoelectric performance to use them in flexible and wearable thermoelectric devices.…”
Section: D Materials In Polymer Thermoelectric Materialsmentioning
confidence: 99%
“…The improvement in carrier mobility is attributed to the band alignment, which attracts hole carriers to CNTs whose mobility is much higher than that of the polymer. In addition, the energy barrier at the interface of CNT and PANI may play an important role [122,123,124,125,126]. Theoretical study suggests that the power factor can be remarkably improved by imposing an energy barrier at the interface of conjugated carbon structures [118,127,128].…”
Section: Cnt‒polymer Compositesmentioning
confidence: 99%
“…The electroactive behavior of PEDOT was utilized not only for control of drug delivery [ 23,24 ] but also for neural engineering by applying redox‐triggered release. [ 25 ] However, PEDOT‐based LBL systems consist of materials (inorganic/organic) other than PEDOT derivatives, [ 1,26 ] and the LBL assembly of only PEDOT derivatives has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al, in 2018, while utilizing electrical conductive properties of PEDOT, demonstrated an enhancement in the thermoelectric property when a PEDOT polymer composite and chemically exfoliated MoS 2 were spin‐coated on the glass surface. [ 26 ] On the other hand, even if the PEDOT was not directly involved as the polymer in LBL, the conductive nature can still be used for different applications, such as in 2017, when Pappa et al used PEDOT: PSS as substrate not as a polymer layer for poly‐L‐lysine and polystyrenesulfonate for LBL assembly to functionalize an organic electrochemical transistor to sense mRNA. [ 32 ]…”
Section: Introductionmentioning
confidence: 99%